2009
DOI: 10.1038/sc.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor blockage with 2-amino-5-phosphonovaleric acid improves oxidative stress after spinal cord trauma in rats

Abstract: Study design: 2-amino-5-phosphonovaleric acid (APV) is an N-methyl-D-aspartate (NMDA) receptor blocker and has neuroprotective properties. This study is aimed at evaluating the effect of APV treatment on oxidative status after spinal cord injury (SCI). Methods: The experiment was carried out on the following five groups: Group1: sham operated, non-traumatized; Group2: with injured spinal cord, no treatment; Group3: with SCI, injected with 100 mg kg À1 APV; Group4: with SCI, injected with 200 mg kg À1 APV; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In the present study, I/R injury decreased SOD activity and increased GSH levels in the spinal cord tissue. Our observations for SOD activity are consistent with those of Vural et al, but not with those of Azbill et al 20,21 Conversely, our findings for GSH levels are consistent with those of Azbill et al, but not with those of Vural et al 20,21 Increased production of TNF-a plays a role in the pathophysiology of SCI. Harrington et al found that at 6 hours post acute SCI, there was increased neuronal expression of TNF-a and its receptors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, I/R injury decreased SOD activity and increased GSH levels in the spinal cord tissue. Our observations for SOD activity are consistent with those of Vural et al, but not with those of Azbill et al 20,21 Conversely, our findings for GSH levels are consistent with those of Azbill et al, but not with those of Vural et al 20,21 Increased production of TNF-a plays a role in the pathophysiology of SCI. Harrington et al found that at 6 hours post acute SCI, there was increased neuronal expression of TNF-a and its receptors.…”
Section: Discussionsupporting
confidence: 92%
“…19 An increase in MDA levels and a decrease in SOD activity and GSH levels have been observed after SCI in animals. 20 However, in another study SOD activity was found to be unchanged at 24 hours following SCI, while catalase activity and GSH level were significantly increased. 21 In our study, I/R injury of the spinal cord was found to increase tissue levels of MDA and AOPP, which is consistent with results reported in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…This result is supported by previous studies that showed that spinal cord ischemia in rabbits increased the mean MDA levels compared to sham-operated animals at 48 h [30] or 72 h [21] after ischemic insults. In a traumatic spinal injury, damage significantly increased MDA levels in the rat spinal cord [31,32]. In the present study, the administration of PEP-1-SOD1 significantly reduced the ischemia-induced increase of MDA in the rabbit spinal cord.…”
Section: Discussionmentioning
confidence: 61%
“…Supporting this idea, superoxide is produced upon NMDA receptor stimulation in cultured cerebellar granule cells [28], and an NMDA receptor antagonist, MK-801, blocks superoxide generation [29]. Moreover, in a rat model of spinal cord injury, decreased SOD and increased MDA were reversed by a NMDA receptor blocker [30]. These data suggest that NMDA receptor activation induces superoxide production, which may in turn, accelerate the central sensitization during the maintenance of the mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%